Evaluating leachate recirculation with cellulase addition to enhance waste biostabilisation and landfill gas production - Frank, R. R.; Davies, Stewart; Wagland, Stuart T.; Villa, Raffaella; Trois, Cristina; Coulon, Frederic (Elsevier, 2016)
The effect of leachate recirculation with cellulase augmentation on municipal solid waste (MSW) biostabilisation and landfill gas production was investigated using batch bioreactors to determine the optimal conditions of moisture content, temperature and nutrients. Experimentation was thereafter scaled-up in 7 L bioreactors. Three conditions were tested including (1) leachate recirculation only, (2) leachate recirculation with enzyme augmentation and (3) no leachate recirculation (control). Cumulative biogas production of the batch tests indicated that there was little difference between the leachate and control test conditions, producing on average 0.043 m3 biogas kg−1 waste. However the addition of cellulase at 15 × 106 U tonne−1 waste doubled the biogas production (0.074 m3 biogas kg−1 waste). Similar trend was observed with the bioreactors. Cellulase addition also resulted in the highest COD reduction in both the waste and the leachate samples (47% and 42% COD reduction, respectively). In both cases, the quantity of biogas produced was closer to the lower value of theoretical and data-based biogas prediction indicators (0.05–0.4 m3 biogas kg−1 waste). This was likely due to a high concentration of heavy metals present in the leachate, in particular Cr and Mn, which are known to be toxic to methanogens. The cost-benefit analysis (CBA) based on the settings of the study (cellulase concentration of 15 × 106 U tonne−1 waste) showed that leachate bioaugmentation using cellulase is economically viable, with a net benefit of approximately €12.1 million on a 5 Mt mixed waste landfill.
Keywords: Leachate circulation; Enzyme augmentation; Waste biostabilisation; Landfill bioreactor